HUBUNGAN PENGETAHUAN KESEHATAN REPRODUKSI DENGAN KUALITAS HIDUP PADA LANSIA DI DESA TONDOMULYO - Zulhijriani; Tri Marlinawati , Iin (Universitas Batam, 2025)
The present study explores the relationship between reproductive health literacy and quality of life among the elderly population in Tondomulyo Village. A cross-sectional methodology was utilized, involving 86 elderly selected through a simple random sampling technique. Data collection employed structured questionnaires to assess reproductive health knowledge and the WHOQOL-BREF instrument for evaluating quality of life. Analysis using Spearman’s rank correlation revealed that 58.1% of participants had sufficient reproductive health knowledge, and 62.8% reported a favorable quality of life. A significant positive correlation was observed between the two variables (p = 0.001, r = 0.624), indicating that higher levels of reproductive health understanding are associated with improved quality of life among the elderly. These results highlight the need for community-based health education programs aimed at enhancing reproductive health awareness to support overall well-being in older populations.